Tobacco use among black South African university students: attitudes, risk awareness and health locus of control - K Peltzer (AOSIS, 2001)
Objectives: To provide data on African/black South African university students' tobacco use status, belief in the benefits to health of not smoking, risk awareness in terms of knowledge of the links between smoking and disease, health locus of control, value for health, subjective health status and well-being. Design: Cross sectional. Setting: University of the North Subjects: 793 Black University students from non-health courses chosen by random sampling, of these 370 (46.7%) were males and 423 (53.3%) were females in the age range of 18 to 25 years (M age 21.0 years, SD=3.48). Main Outcome Measures: A measure of smoking, the Multidimensional Health Locus of Control Scale, the Health as a Value Scale, and a measure for subjective health and subjective well-being. Results: The average prevalence of current tobacco use was 15% in men and 1% in women. The proportion of tobacco users who were classified as light users (1-10 per day) averaged 10% in men and 1% in women. Age and being male were significantly positively associated with status and frequency of tobacco use. Awareness of the link between smoking and lung cancer was high (93%), but awareness of the role of smoking in heart disease was very low (16%). The importance to health of not smoking was associated with smoking status (non-smoking versus smoking). Overall, 75% of the current smokers stated that they would like to reduce the amount they smoked. Poor subjective health status and low subjective well-being was associated with smoking status. No significant differences were found among non-tobacco users and tobacco users in relation to the three subscales of the Health Locus of Control (Internal, Chance, and Powerful others) and Value for health. Conclusion: For about 9% of the male students investigated, a high risk exists to become regular tobacco users for the next 30 years.